Traumatisme et mémoire culturelle - Treskow, Isabella <<von>>,Segler-Meßner, Silke (De Gruyter, 2023)
In the francophone world of the 20th and early 21st centuries, collective violence, trauma and mediatization interact with each other. World Wars, wars of independence and decolonization, the Shoa, exile, migration and terrorism cause traumas which are mediatized in text and image, but also in commemorative rites, music, the press or museums. This volume provides an analysis of these media as well as a presentation of the theoretical framework. Contains contributions by: Angela Kühner, Frankfurt am Main (Germany); Nathalie Maillard, Montréal (Canada); Boris Cyrulnik, Bordeaux (France); Catherine Wermester, Paris I Sorbonne (France); Rémi Dalisson, Rouen (France); Pierre Schoentjes, Gent (Belgium); Laurence Campa, Paris-Nanterre (France); Vincent Marie, Nîmes (France); Christian von Tschilschke, Siegen (Germany); Nathalie Piégay, Paris VII Diderot (France); Peter Kuon, Salzburg (Austria); Dominique Trouche, Toulouse (France); Jonas Hock, Regensburg (Germany); Christian Delage, Paris VIII (France); Fransiska Louwagie, Leicester (United Kingdom); Yoram Mouchenik, Paris XIII (France); Esther Kilchmann, Hamburg (Germany); Catherine Milkovitch-Rioux, Clermont-Ferrand (France); Sarah Kouider Rabah, Blida (Algeria); Susanne Gehrmann, Berlin (Germany); Olivier Barlet, Paris (France); Hans-Jürgen Lüsebrink, Saarbrücken (Germany); Alexandre Dauge-Roth, Lewiston (United States); Delphine Robic-Diaz, Tours (France); Anja Bandau, Hannover (Germany); Christoph Singler, Besançon (France); Françoise Naudillon, Concordia (Canada); Elisabeth Nardout-Lafarge, Montréal (Canada); Isaac Bazié, Montréal (Canada); Nicolas Violle, Clermont-Ferrand (France); Isabelle Galichon, Pau/Bordeaux (France); Karim Hammou, Paris (France)
9783110355840
Keywords: Aufsatzsammlung; Frankreich; Französische Literatur; Geschichtswissenschaft Allgemein; Europa; Europäische Literatur; Gewalt und Diskriminierung: Soziale Aspekte; Hardcover; Softcover / Geschichte/Kulturgeschichte; Literary studies: general; Literary studies: from c 1900 -; Social & cultural history; Memory; HIS000000 HISTORY / General; LIT000000 LITERARY CRITICISM / General; LIT004130 LITERARY CRITICISM / European / General; LIT025000 LITERARY CRITICISM / Subjects & Themes / General; SOC000000 SOCIAL SCIENCE / General; SOC051000 SOCIAL SCIENCE / Violence in Society; Trauma; Kollektives Gedächtnis; Geschichte/20. Jahrhundert; Geschichte/21. Jahrhundert; Französischer Kulturraum; Collective Memory; 20th-Century History; 21st-Century History; Francophone Cultures